Music and Dance: The comparison between non-dancer’s aesthetic experience and their Bodily sensations - Vukadinović, Maja (Psihološka istraživanja, 2023)
This paper aims at investigating and comparing the observers’ aesthetic experience and their bodily sensations in two different settings: when only listening to music and when watching dance choreographed to that particular music. The study included 209 students, non-dancers and non-musicians, aged between 17 and 27 (M = 19.39, SD = 1.37, 70.3% women) from Novi Sad Business School. The stimuli consisted of six audio-visual recordings of original dance performances including three contemporary and three hip hop pieces. The stimuli were presented in two different settings: in the first one, the participants only listened to the audio recordings of the music and in the second one they watched the audio-visual recordings of the choreographies made for that particular music. Each piece was assessed on two scales, one measuring the structure of aesthetic experience on three dimensions (Dynamism, Affective Evaluation and Exceptionality) and the other measuring the structure of bodily sensations (Focus, Excitement and Embodied Anticipation). The results have shown that the setting (music only/dance to music) had a statistically significant effect on the students’ assessments of their aesthetic experience and bodily sensations. The participants’ assessments of the dimensions of Affective Evaluation, Exceptionality and Focus were significantly higher when they watched dance choreographies made to the music which they had previously only listened to. Based on these results, it has been concluded that the higher the participants’ assessment of the delicacy, elegance and their attention to dance movements is, the higher is their engagement with the piece.